Impulsive mode elimination for descriptor systems by a structured P-D feedback - Zhang, G.; Liu, Wan-Quan (IEEE, 2011)
The problem of impulsive mode elimination for descriptor systems via a structured output proportional and derivative (P-D) feedback isinvestigated in this technical note. The motivation of solving this problem arises from an observation that the impulse behavior for some descriptorsystems can not be eliminated completely by a parameterized output P-D feedback, but it can be removed by a structured P-D feedback elegantly designed. In order to explain this phenomenon explicitly, a concept of the structured P-D feedback is first introduced, then an explicit necessary and sufficient condition is constructively derived for the closed loop systems to be regular and impulse-free by the structured P-D feedback. The main result is represented in terms of the original system parameters instead of decomposed subsystem parameters. Finally, an example is provided to illustrate the effectiveness of the proposed result.